2019
DOI: 10.1371/journal.pone.0218106
|View full text |Cite
|
Sign up to set email alerts
|

Understanding illness perception in pulmonary tuberculosis patients: One step towards patient-centered care

Abstract: Background Assessing the illness perception of patients with tuberculosis (TB) could improve our understanding of their beliefs about disease and help address problems in their health-seeking behavior. Study aim We assessed illness perception in patients with pulmonary TB in association with patients’ demographic, socioeconomic, and clinical features. Methods Adult patients who were newly diagnosed with pulmonary TB at three tertiary hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
(29 reference statements)
1
11
1
1
Order By: Relevance
“…The lowest score on "identity" conveys that people were ill-informed about COVID-19 pandemic. The findings of "timeline" and "concern" contradict previous study (Min et al, 2019) as the current study participants were not worried about being infected by the COVID-19 and they perceived that current pandemic will not continue for a long time, which might be caused by the culturally misleading communications about COVID-19 as noninfectious disease or a disorder without serious complications. The low score on "emotional response" dimension of the current study can be connected to less dangerous perceptions of the pandemic situation; in which feelings of anxiety or fear are less evident or the risk of contracting the COVID-19 is manageable.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…The lowest score on "identity" conveys that people were ill-informed about COVID-19 pandemic. The findings of "timeline" and "concern" contradict previous study (Min et al, 2019) as the current study participants were not worried about being infected by the COVID-19 and they perceived that current pandemic will not continue for a long time, which might be caused by the culturally misleading communications about COVID-19 as noninfectious disease or a disorder without serious complications. The low score on "emotional response" dimension of the current study can be connected to less dangerous perceptions of the pandemic situation; in which feelings of anxiety or fear are less evident or the risk of contracting the COVID-19 is manageable.…”
Section: Discussioncontrasting
confidence: 86%
“…In the current large scale multi‐Arab countries study, the majority of respondents showed a lower perception of illness and threat of COVID‐19 pandemic. Illness perceptions are the organized cognitive representations or beliefs that people have about their diseases, and it is an important determinant of compliance with any resulted precautionary behaviors (Min et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge influences perception [ 29 , 30 , 31 , 32 ]. Perception about illness is the patient’s experience with the disease suffered and that experience will be applied to his or her condition [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 Meanwhile, they are also asked to make numerous behavioural in dietary and lifestyle changes, and undergo multiple hospital admissions to be examined. 3,4 Thus, consistent adherence to treatment is key for TB patients to achieve good therapeutic outcomes. However, the complex treatment process may result in patients with myriad unmet supportive care needs (SCN), which in turn impair their compliance and lead to poor health outcomes.…”
Section: Introductionmentioning
confidence: 99%